Organic carbon distribution in an Oxisol under phosphate fertilizer management and no‑tillage in the Cerrado - Jerke, Caroline; Sousa, Djalma Martinhão Gomes de; J. Goedert, Wenceslau (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the vertical and horizontal distribution of soil organic carbon (SOC) under five managements of phosphate fertilizer in a no‑tillage system. The experiment was established on a Rhodic Haplustox, cultivated with soybean or corn for eight years, with millet as cover crop during the off-season. Plots were subjected to the following treatments: triple superphosphate in the sowing furrow or on surface, reactive natural phosphate on the sowing furrow or on surface, and without the addition of phosphate fertilizer (control). Phosphate fertilizer was applied annually at a dosage of 80 kg ha‑1 of P2O5 on soil initially with a low phosphorous content. Samples were collected perpendicularly to the sowing line in seven sites distanced at 12.5 cm, and in five layers: 0–2.5, 2.5–5.0, 5.0–10, 10–20, and 20–30 cm. The content and the distribution of SOC are vertically and horizontally affected by phosphate fertilization, with higher contents in treatments with phosphate fertilizers. Compared to the control treatment, triple superphosphate showed higher SOC concentrations until the 5.0–10‑cm layer, and reactive natural phosphate until 10–20 cm. Phosphorus application in furrows provides greater volume of soil with suitable levels of SOC, compared to broadcast application.